Exploring the dynamics of fintech usage behavior moderated by customer characteristics in Indonesia - Cahyadi, Hadi; Tarigan, Ribka Putrita; Masman, Ronnie Resdianto; Trisnawati, Estralita; Wijaya, Henryanto (International Journal of Innovative Research and Scientific Studies, 2024)
This research examines the factors influencing the adoption of Fintech services in Indonesia, focusing on perceived risk, perceived benefit, perceived usefulness, perceived ease of use, trust, and Fintech usage intention. Data from 317 users of payment Fintech services in Indonesia was collected through a Google Form questionnaire and analyzed using Smart PLS 4.0. The study reveals that perceived usefulness, perceived ease of use, and trust significantly impact Fintech usage intention and subsequent behavior, particularly among millennials and Gen Z. Customer attributes such as age and gender show minimal impact, while education level, especially advanced degrees, strengthens the link between perceived usefulness and intention to use. The results contribute to understanding the Fintech sector in Indonesia and suggest potential areas for future research. The study is limited to payment Fintech in Indonesia and recommends broadening the scope for future research. To enhance future research, it is recommended to broaden the study scope to include various fintech types, expand the geographical coverage for diverse results, and encompass a wider range of ages and education levels among respondents for a more comprehensive understanding of fintech adoption.